Heterogeneous Nucleation onto Monoatomic Ions: Support for the Kelvin‐Thomson Theory. Issue 22 (12th October 2018) - Tauber, Christian; Chen, Xiaoshuang; Wagner, Paul E.; Winkler, Paul M.; Hogan, Christopher J.; Maißer, Anne
Abstract: In this study, the process of heterogeneous nucleation is investigated by coupling a high‐resolution differential mobility analyser (DMA) to an expansion‐type condensation particle counter, the size‐analyzing nuclei counter (SANC). More specifically, we measured the activation probabilities of monoatomic ions of both polarities by using n‐butanol as condensing liquid. All seed ions were activated to grow into macroscopic sizes at saturation ratios well below the onset of homogeneous nucleation, showing for the first time that the SANC is capable of detecting sub‐nanometer sized, atomic seed ions. The measured onset saturation ratios for each ion were compared to the Kelvin‐Thomson (KT) theory. Despite the fact that certain dependencies of activation behaviour on seed ion properties cannot be predicted by the KT theory, it was found that with a simple adjustment of the n‐butanol molecular volume (9–15 % lower compared to bulk properties) good agreement with experimental results is achievable. The corresponding density increase may result from the dipole‐charge interaction. This study thus offers support for the application of the KT model for heterogeneous, ion‐induced nucleation studies at the sub‐nanometer level. Abstract : Heterogeneous nucleation on monoatomic seed ions : Size‐selected monoatomic ions are used as nucleation seeds to investigate heterogeneous nucleation. The onset saturation ratios are measured with an expansion chamber (size analysing nuclei counter, SANC) and compared to predictions based on the Kelvin‐Thomson Model.